Factors Influencing HPV Vaccination Intention in Mothers with Elementary School Daughters - Sun Hwa Kim; Mi Hae Sung; Yun Ah Kim; Hye Jin Park (Korean Society of Women Health Nursing, 2019)
PURPOSE: The purpose of this study was to identify the impacts of human papillomavirus (HPV) vaccination-related health belief, attitudes toward HPV vaccination, and subjective norms on HPV vaccination intent targeting mothers of elementary school daughters. METHODS: The study use a correlative survey design. The subjects of the study were 121 mothers of elementary school daughters located in metropolitan city B. All subjects agreed to participate in the study. The data were collected from September 1 to October 18, 2018, and were analyzed using descriptive statistics, Independent t-test, ANOVA with a post hoc Scheffé test, Pearson's correlation coefficients, and stepwise multiple regression. RESULTS: Attitude toward HPV vaccination, subjective norms, vaccination plans for their children, and mother's vaccination status were significant factors influencing HPV vaccination intention. These factors accounted for 72% of the HPV vaccination intention. CONCLUSIONS: This study showed that factors affecting the intention of mothers of elementary school daughters to vaccinate against HPV were HPV vaccination attitudes, subjective norms, vaccination plans for their children, and mother's vaccination status. The biggest influencing factor was HPV vaccination attitudes. Therefore, in order to encourage mothers of elementary school daughters to vaccinate against HPVs, national-level policies should be implemented to create a social atmosphere of positive attitudes toward HPV vaccinations that also emphasizes how easy it is to get vaccinated against HPV. Based on this, mothers of elementary school daughters should be encouraged to have them vaccinated against HPV, thus contributing to improving the HPV vaccination rates of elementary school girls.